Studies on freshwater entomostraca in Greenland II. Localities, ecology and geographical distribution of the species - Røen, Ulrik Ib (Meddelelser om Grønland, 1962)
A survey has been made of the freshwaters of Greenland, based on 207 localities-64 lakes, 107 ponds, and 36 temporary waters. Tables are given with information about conductivity, hydrogen ion concentration, alkalinity, acidity, consumption of potassium permanganate, colour, and contents of Ca++, Mg++, Cl-, Fe++, and total iron in most of the localities. An attempt is made to divide lakes, ponds and temporary waters into types. Freshwater entomostraca have been collected from the 207 localities, and further investigations have been made on collections from 118 localities which the author himself has not examined. 52 species of freshwater entomostraca have been examined, eight of which are new to Greenland. Four previously recorded species have not been found again. The distribution of the species is viewed in relation to a number of physicochemical conditions found in the localities investigated. The distribution of various species in Greenland is shown on a number of maps. On the basis of these maps and the percentage occurrence of the species within 11 areas of distribution into which Greenland is divided, a division of the species into four faunal elements has been made, viz. an element found in the whole of Greenland, a northwestern element, a southern element, and a brackish water element. Errata: Page 123, locality 135, first line: for “pudde” read “puddle” Page 165, Maraenobiotus brucei Greenland records, second line: for “Johansen (1913)” read “Johansen (1912)”